Building a Bridge from Papermaking to Solar Fuels. Issue 42 (3rd September 2019) - Jiang, Zaiyong; Zhang, Xinhan; Sun, Wei; Yang, Deren; Duchesne, Paul N.; Gao, Yugang; Wang, Zeyan; Yan, Tingjiang; Yuan, Zhimin; Yang, Guihua; Ji, Xingxiang; Chen, Jiachuan; et al.
Abstract: Black liquor, an industrial waste product of papermaking, is primarily used as a low‐grade combustible energy source. Despite its high lignin content, the potential utility of black liquor as a feedstock in products manufacturing, remains to be exploited. Demonstrated here in is the use of black liquor as a primary feed‐stock for synthesizing graphene quantum dots that exhibit both up‐conversion and photoluminescence when excited using visible/near‐infrared radiation, thereby enabling the photosensitization of ultraviolet‐absorbing TiO2 nanosheets. In addition, these graphene quantum dots can trap photo‐generated electrons to realize the effective separation of electron‐hole pairs. Together, these two processes facilitate the solar‐powered generation of H2 from H2 O, and CO from H2 O–CO2, using broadband solar radiation. Abstract : Black liquor, an industrial waste product of paper‐making, is primarily used as a low‐grade combustible energy source. Herein, the successful preparation of graphene quantum dots (GQDs) using black liquor as a precursor is reported. The obtained GQDs display excellent photoluminescence down‐ and up‐conversion activity which are exploited to improve the photocatalytic H2 O and CO2 reduction activities of TiO2 .